2010
DOI: 10.1007/s00264-010-1118-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of isolated popliteus tendon complex injury on graft force in anterior cruciate ligament reconstructed knees

Abstract: Failure to diagnose injury to the posterolateral structures has been found to increase the forces experienced by the anterior cruciate ligament (ACL) and ACL grafts which may cause their subsequent failure. An isolated injury to the popliteus complex (PC) consisting of the popliteus tendon and popliteofibular ligament is not uncommon. Therefore, the purpose of this study was to discover if an isolated injury to the PC can significantly affect the forces experienced by the ACL graft under external loading condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…The structures of the PLS can be divided into two primary components: the lateral collateral ligament (LCL) and the popliteus complex (PC; Ullrich et al 2002;Zantop et al 2007;Gadikota et al 2010;Jung et al 2010;Yang et al 2011). The PC consists of the popliteus muscletendon unit, i.e., the popliteus tendon (PT), and the ligamentous connections between PT on one hand, and the fibula and meniscus on the other hand, i.e., the popliteofibular ligament (PFL) and popliteomeniscal fascicles (Ullrich et al 2002;Zantop et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The structures of the PLS can be divided into two primary components: the lateral collateral ligament (LCL) and the popliteus complex (PC; Ullrich et al 2002;Zantop et al 2007;Gadikota et al 2010;Jung et al 2010;Yang et al 2011). The PC consists of the popliteus muscletendon unit, i.e., the popliteus tendon (PT), and the ligamentous connections between PT on one hand, and the fibula and meniscus on the other hand, i.e., the popliteofibular ligament (PFL) and popliteomeniscal fascicles (Ullrich et al 2002;Zantop et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To better understand this complex area, many investigations have attempted to define the quantitative anatomy and specific function of PC through laboratory, radiographic, and surgical studies(Pasque et al 2003;LaPrade et al 2003;Wadia et al 2003;Ishigooka et al 2004;Moorman and LaPrade 2005;Gadikota et al 2010;Jung et al 2010;Yang et al 2011). These fundamental studies have demonstrated that the PC consists of the popliteus muscle-tendon unit, PFL and the popliteomeniscal fascicles(Ullrich et al 2002;Zantop et al 2007).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…The lateral patellofemoral ligament, popliteus tendon, popliteofibular ligament, and fabellofibular ligament have all been described in detail [3,[9][10][11][12][13]], but to date descriptions of the attachments of the LCL remain incomplete in the published literature.…”
Section: Discussionmentioning
confidence: 99%